The performance of TCP over ATM networks - Wang, Yuyang. (2008)
One of the problems in transmitting TCP/IP traffic over ATM networks is that a TCP/IP packet is transported over several ATM cells, and whenever a single cell is lost in the ATM network, the whole packet has to be discarded, causing a waste of bandwidth to transmit the other cells of the packet. EPD (Early Packet Discard) technique was then proposed for UBR to improve the performance by emulating the traditional packet switched network. The other way to deal with this problem is to employ the ABR congestion control mechanism to minimize the cell loss ratio in the ATM network. However, the performance of TCP over the traditional binary mode ABR is found to be too unstable, i.e. too sensitive to the parameter tunings and the network topology. We proposed a new congestion judgment scheme for binary mode ABR to improve the performance robustness. TCP over ER mode ABR is also evaluated, in both the LAN and WAN environments. At last, the interoperability between the new binary mode ABR and ER mode ABR schemes is investigated.